Sociological and spatial dynamics of an evolving Parisian open drug scene: the case of the "Colline du Crack". Issue 3 (3rd August 2021) - Jangal, Candy; Lovera, Mathieu; Dambélé, Sayon; Jauffret-Roustide, Marie
Abstract : Purpose: In November 2019, an open drug scene, commonly called "Colline du crack" and located in Paris was forcibly closed after 10 years of existence. This paper aims to understand how that space has evolved over the years to become a major hub for drug use. Design/methodology/approach: The authors used a qualitative approach that included interviews with 52 people who use drugs (PWUD) and 54 field professionals and ethnographic observations. The authors asked questions about the evolution of the major sites of crack visibility in Paris and about social representations related to these spaces. They compared their datas with datas drawn from gray literature. Findings: La Colline emerged on an isolated slope, away from police repression and local anti-crack organizations. In the beginning, it was a discrete, communal space regulated by PWUD. Starting in 2015, social transformations in the neighborhood turned la Colline into a central hub for dealing and using crack. La Colline became an open scene which led to its evacuation in 2019. Originality/value: This paper contributes to literature on community building of drug consumers. The authors are also using a wide variety of methodological tools.